2019
DOI: 10.3389/fmolb.2019.00066
|View full text |Cite
|
Sign up to set email alerts
|

A “One-Stop” Screening Protocol for Haemoglobinopathy Traits and Iron Deficiency in Sri Lanka

Abstract: Introduction: The high frequencies of carriers of severe haemoglobinopathies and of iron deficiency in Southeast Asia require reliable and affordable tests to improve on current screening procedures. Objectives: We evaluate a “one stop” approach using the THALCON dichlorophenolindophenol (DCIP) and one-tube osmotic fragility (OF) tests and measurement of Zinc Protoporphyrin (ZPP) to detect and distinguish HbE and β-thalassaemia traits from iron deficiency. We compare findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The facilities for screening for thalassaemia are available throughout the country for free [ 31 , 32 ]. The low figure reported in our study highlights that despite its existence for over 15 years, the National Thalassaemia Prevention Programme has not been able to deliver the message to the public [ 12 ]. In a recent study done among 245 females diagnosed with anaemia during pregnancy, we found that 18 had undiagnosed β-thalassaemia trait, which was not recognised up to the pregnancy [ 33 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The facilities for screening for thalassaemia are available throughout the country for free [ 31 , 32 ]. The low figure reported in our study highlights that despite its existence for over 15 years, the National Thalassaemia Prevention Programme has not been able to deliver the message to the public [ 12 ]. In a recent study done among 245 females diagnosed with anaemia during pregnancy, we found that 18 had undiagnosed β-thalassaemia trait, which was not recognised up to the pregnancy [ 33 ].…”
Section: Discussionmentioning
confidence: 95%
“…Thalassaemia trait is an asymptomatic condition which results in mild microcytic anaemia [ 11 ]. It does not require any treatment; however, the affected individuals should avoid marrying a partner with thalassaemia trait to prevent the birth of a child with severe homozygous forms of thalassaemia (thalassaemia major) [ 12 ]. The prevalence of β- and α-thalassaemia traits in Sri Lanka is reported as 2.8% and 8%, respectively [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, screening for thalassaemia by performing haemoglobin highperformance liquid chromatography (HPLC) or capillary electrophoresis (CE) is recommended for all children with microcytic anaemia with or without iron deficiency. The diagnosis of -thalassaemia trait is confirmed if the patient has haemoglobin A2 >3.4% 20 .…”
Section: Diagnosismentioning
confidence: 99%
“…Several strategies (78) are available and the regional experience in Sri Lanka could be instructive (79) . An advocacy effort might work to gain support for furthering research and development into rapid screening which could test for haemoglobinopathies and Fe deficiency in one test, as demonstrated in a recent study conducted in Sri Lanka (80) .…”
Section: Clinical Strategiesmentioning
confidence: 99%